2018
DOI: 10.1111/jfd.12869
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus sequence typing reveals clonality in Saprolegnia parasitica outbreaks

Abstract: The molecular epidemiology of fish pathogen Saprolegnia parasitica is still largely unknown. We developed a multilocus sequence typing scheme based on seven housekeeping genes to characterize 77 S. parasitica strains isolated from different fish host species at different times and from different geographic areas in Switzerland between 2015 and 2017. Ten different diploid sequence types (DSTs) were identified. The majority (52%) of outbreaks in Switzerland seemed to be caused by one genotype, namely DST3, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 31 publications
1
21
1
Order By: Relevance
“…A partial 18S region of the nrDNA was amplified using 18sF (5′-AGGAATTGACGGAAGGGCAC-3′) and 18sR (5′-TGATCCTTCCGCAGGTT-3′) primer pairs (Spencer et al, 2002). The Cox1 and Cox2 regions were amplified using primer pairs developed by Hudspeth, Nadler, and Hudspeth (2000) and Ravasi, De Respinis, and Wahli (2018). All PCRs were prepared and run according to the protocol described by Sarowar et al (2019).…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 99%
“…A partial 18S region of the nrDNA was amplified using 18sF (5′-AGGAATTGACGGAAGGGCAC-3′) and 18sR (5′-TGATCCTTCCGCAGGTT-3′) primer pairs (Spencer et al, 2002). The Cox1 and Cox2 regions were amplified using primer pairs developed by Hudspeth, Nadler, and Hudspeth (2000) and Ravasi, De Respinis, and Wahli (2018). All PCRs were prepared and run according to the protocol described by Sarowar et al (2019).…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 99%
“…Clinical signs included anorexia, lethargy, skin ulcerations, multifocal hemorrhages, and eroded tail fins. Culture and PCR indicated that skin ulcerations were caused by oomycete ( Saprolegnia parasitica ) infection ( 21 ). Histopathology revealed mild to moderate gill epithelial proliferation and epithelial cell hypertrophy.…”
Section: Resultsmentioning
confidence: 99%
“…Existing studies on S. parasitica mostly focus on its negative impacts in aquaculture: it is responsible for significant economic losses in salmonid farms and hatcheries worldwide 3 , 5 , and aquaculture facilities can act as pathogen pools from which S. parasitica spreads to natural environments 6 , 7 . In comparison, the potential negative impacts of S. parasitica on wild populations of salmonids and other animals remain largely unexplored, although declines in wild salmon populations caused by saprolegniosis have been reported 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Humic substances, which constitute the majority of dissolved organic matter in oligotrophic freshwater ecosystems, can inhibit mycelial growth of the pathogen 16 , while Ca 2+ ions regulate processes such as adhesion, encystment and germination 11 , 17 . Despite numerous laboratory studies, knowledge about the prevalence of S. parasitica in the natural environment is very limited 9 , 18 20 , making it impossible to define the pathogen's distribution range and analyse ecological parameters that could influence its occurrence. Determining the relationship between the ecological and physico-chemical status of natural waters and the occurrence of S. parasitica is central to any attempt to predict the possibility of disease outbreaks in a realistic natural setting.…”
Section: Introductionmentioning
confidence: 99%